Electrician not electrishion? Implicit and explicit knowledge of word stem and affix morphemes for children’s spelling - Burton, L (2019)
This study investigated the extent to which implicit and explicit knowledge of morphology contribute to children’s spelling in English. Children acquire some understanding of morphemes for spelling through their everyday encounters with words, but this could be enhanced to a more explicit level through direct instruction. Intervention studies have reported the advantage of teaching children about morphemes for spelling, but the vast majority of this research has been restricted to affixes, with limited attention to teaching word stems or combining instruction of stems and affixes together. In response, the current study compares a child’s knowledge of morphemes with implicit or explicit instruction of two related morphological spelling rules: the conservation of word stems in derived words and the distinction between the affixes of -ion and -ian.